Menentukan Intensitas Radiasi UV yang Diterima Pekerja Pengelasan dengan Titik Area Mata, Siku, dan Betis - Muliana Dai; Kadek Subagiada; Adrianus Inu Natalisanto (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2021)
The aim of this study is to measure the UV intensity received by the welders during working time and compare the results of measured radiation intensity which is obtained with the NAB in Regulation of the Minister of Manpower No. 05 of 2018 that is 0,0008 mW/cm2. The reason for using this NAB is for compare value while welding process with the value were allowed from Regulation of the Minister of Manpower. This study has been done in some workshops using the UV Meter and focused on the welders’ eye, elbow and calf area with 10 repetitions in each area. The results for eye area were 0.0749 mW/cm2, for elbow area were 0.0843 mW/cm2and for calf area were 0.0934 mW/cm2and all the results obtained exceed the NAB. The high value is caused by the environmental conditions is open and also affected by indeterminate sunlight, the risks received the welders in watery eye and headache because of the welder are disobey in using PPE while welding process.